A espacialização dos vazios urbanos em Londrina (PR) - Agnaldo da Silva Nascimento (Confins)
During the recent years, the urban space production is subordinated to the real state capital reproduction, mostly by the land ownership appreciation. In the cities production the agents involved produce or reproduce the urban morphology, where adds up the physical shapes, process and contents aspects. In the urban delimited perimeter are contained many elements that make up the urban context, for example, the urban voids that have a significant presence in cities. In this direction, this paper target a discussion with emphasis on urban voids, questioning their presence in the Londrina (PR) mediator city in Brazil. First, it was considered that the existence, maintenance and multiplication of these urban elements are included in the landscape, has been one cities production indicative from the capital reproduction, which is evidenced by the significant speculation process presence. This urban process coming in one less uneven city detriment, increasing the urban segregation which results the social inequality. The discussion focused on the Londrina urban area expansion looking for the urban voids origins, formation and retention. It was based in the city's expansion history and the ways in which urban voids are part spatially and quantitative data drawn from satellite images through remote sensing and GIS in which it was done collecting the spatial treatment. The methodology results generated the cartographic products that allow analyzing the Londrina urban expansion process and the urban voids spatial distribution, and also was identify that the city has around 50% of its urban area with the urban voids presence.